2017
DOI: 10.5578/mb.57333
|View full text |Cite
|
Sign up to set email alerts
|

Klinik Klebsiella pneumoniae İzolatlarında Karbapenemaz Üretiminin Saptanmasında Polimeraz Zincir Reaksiyonu ve Fenotipik Yöntemlerin Karşılaştırılması

Abstract: Being a member of the Enterobacteriaceae family, Klebsiella pneumoniae is an opportunistic pathogen that inhabits normal human microbiota and causes predominantly hospital-acquired infections. The emergence of K.pneumoniae isolates which are resistant particularly to the carbapenem group of antibiotics has led to an increase in hospitalization period, mortality and morbidity. Although different rates of resistance are observed between countries, regions and even healthcare facilities, there has been a rapid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The K. pneumoniae strain producing NDM carbapenemase in Turkey was first identified from the patient's blood culture in 2011 [12]. It was the second most isolated carbapenemase gene type in Turkey after OXA-48 [13][14][15][16]. In our study, while the NDM gene was single in 21 strains and co-existed with OXA-48 in 18 strains in a total of 39 NDM (78%)-carrying strains, OXA-48…”
Section: Discussionmentioning
confidence: 46%
“…The K. pneumoniae strain producing NDM carbapenemase in Turkey was first identified from the patient's blood culture in 2011 [12]. It was the second most isolated carbapenemase gene type in Turkey after OXA-48 [13][14][15][16]. In our study, while the NDM gene was single in 21 strains and co-existed with OXA-48 in 18 strains in a total of 39 NDM (78%)-carrying strains, OXA-48…”
Section: Discussionmentioning
confidence: 46%
“…In the same study, KPC was identified in four strains ( 15 ). In another study conducted in our region in 2017, no KPC-producing strain was found ( 6 ). In this study, 20 strains were found to be producing KPC.…”
Section: Discussionmentioning
confidence: 93%
“…Primers targeting the bla NDM , bla OXA-48 , bla KPC , and bla VIM were used in carbapenem-resistant isolates ( 6 , 7 ). The final ingredient of the PCR mix was prepared as; X Taq Buffer, 200 mm dNTP, 2.5 mm MgCl 2 (Taq polymerase - set dNTP, Applied Biological Materials Inc., Canada), and 50 pmol of primer pairs in a final volume of 25 μL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IMP direnç geni Japonya ve Tayvan' da endemik iken VIM direnç geni ise Yunanistan'da endemiktir (1,5,13) . Ülkemizde yapılan çeşitli çalışmalarda, tekli direnç geni OXA-48 varlığı en sık direnç mekanizması, OXA-48 ve NDM-1 direnç geni birlikteliği ise ikinci sıklıkta bildirilmiştir (21)(22)(23)(24) .…”
Section: Discussionunclassified